A Smart Way of Making Dental Practice Painfree - Kajal Kiran Sahoo1 , Sudipta Sahu2 , Debashruti Naik3 , Nikita Sahu3 , Sarmistha Mohanty4 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Local anaesthesia in dentistry has been used in dentistry for more than a century ago. The emergence ofgiving local anaesthesia through nerve blockade marked a new era of patient comfort while permitting moreextensive and invasive procedure in dental practice. Though ages effective LA is the most important pillarupon which systems have been developed that utilizes computer technology in the LA administration. Thecore mechanics behind the Computerised controlled local anaesthesia Device (CCLAD) is a microprocessorthat controls delivery of LA solution at constant pressure and controlled volume while monitoringthe variation in the tissue resistance. This fine high suffusion flow rate of LA provides a rapid onset ofanaesthesia in most dental patients. Although local anaesthesia in injection form remains the backbone ofpain control in dentistry, researches are being made in constant search of new & better management of pain.These researches are focused on the advancement of local anaesthetic agent delivery devices and techniquesinvolved in both pharmacological and non-pharmacological form. Paradoxically the injection of LA seemsto be the greatest source of patients fear and inability to control pain remains a significant concern to thedental practitioner. This review article will aim towards the products, device and techniques available tillnow which will make dentistry more patient-friendly and non-invasive.